Indications and limits for modular endoprosthetic reconstruction by MUTARS implants in patients with malignant bone tumor (literature review) - Vyrva, Oleg; Golovina, Yanina; Burlaka, Victor; Baev, Vitaliy; Shevchenko, Igor; Malyk, Roman; Mikhanovsky, Dmytro; Golovina, Olga; Vyrva, Oleksandra; Yutovets, Yuriy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Modular tumor prostheses are well established today for the reconstruction of osseous defects after resection of malignant bone tumors. Almost every joint and even total bones (e. g., total femur or humerus) can be replaced with promising functional results dramatically reducing necessity for ablative procedures. During the last 30 years the 5-year survival rate of megaendoprostheses increased from 20 to 85 %. Although the complication rate with the use of the modern modular endoprostheses is constantly decreasing it is still significantly higher than in primary joint arthroplasty. Together with local tumor recurrence periprosthetic infection remains the most severe complication. Due to constant improvements of prostheses material and surgical techniques, the indications and limits of limb salvage with modular tumor prostheses are continuously changing and to some extent might have to be reconsidered. The typical indication for modular endoprostheses is a large osseous defect after resection of a malignant bone tumor of the metadiaphyseal region of a long bone in the upper or lower extremity. Involvement of major vessels to the tumor is still considered as a contraindication to limb salvage surgery. But limb salvage can nowadays be performed with modular endoprostheses and vascular reconstruction with good oncological and functional results.The functional results after reconstruction of bone defects in tumor surgery are good and can be scored according to Enneking score. In this review authors present the modular endoprosthetic systems MUTARS developed by Implantcast (Buxtehude, Germany) with discussion the indications and contraindications, complications and functional outcomes as well as a surgical technique and postoperative management this category of the patients.